2018
DOI: 10.1113/jp276923
|View full text |Cite
|
Sign up to set email alerts
|

Differential targeting and signalling of voltage‐gated T‐type Cav3.2 and L‐type Cav1.2 channels to ryanodine receptors in mesenteric arteries

Abstract: Recent data suggest that T-type Ca 3.2 channels in arterial vascular smooth muscle cells (VSMCs) and pits structure of caveolae could contribute to elementary Ca signalling (Ca sparks) via ryanodine receptors (RyRs) to cause vasodilatation. While plausible, their precise involvement in igniting Ca sparks remains largely unexplored. The goal of this study was to elucidate the contribution of caveolar Ca 3.2 channels and their functional interaction with Ca 1.2 channels to trigger Ca sparks in VSMCs from mesente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 52 publications
(154 reference statements)
6
37
0
Order By: Relevance
“…The T‐type Ca v 3.2 channel blocker Ni 2+ decreased Ca 2+ spark frequency and fraction of cells with sparks in young VSMCs (see also (Fan et al, 2018; Hashad et al, 2018)), while it failed to decrease Ca 2+ spark events in old VSMCs (Figure 1). These data suggest that Ca v 3.2 channels contribute to generation of Ca 2+ sparks in young but not in old VSMC.…”
Section: Resultsmentioning
confidence: 74%
See 4 more Smart Citations
“…The T‐type Ca v 3.2 channel blocker Ni 2+ decreased Ca 2+ spark frequency and fraction of cells with sparks in young VSMCs (see also (Fan et al, 2018; Hashad et al, 2018)), while it failed to decrease Ca 2+ spark events in old VSMCs (Figure 1). These data suggest that Ca v 3.2 channels contribute to generation of Ca 2+ sparks in young but not in old VSMC.…”
Section: Resultsmentioning
confidence: 74%
“…The data also show that SR Ca 2+ load is controlled by SERCA (Nelson et al, 1995). We next studied how Ca v 1.2 channel ablation and reduced [Ca 2+ ] SR load affect the Ca V 3.2‐RyR axis, that is, direct coupling between Ca V 3.2 channels and RyRs to generate Ca 2+ sparks (Fan et al, 2018; Hashad et al, 2018; Löhn et al, 2000). Consistent with our previous results (Essin et al, 2007), we found that [Ca 2+ ] SR was lower in Ca v 1.2 −/− (SMAKO) VSMCs compared to Ca v 1.2 +/+ control cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations